AIE-active mechanochromic materials based N-phenylcarbazol-substituted tetraarylethene for OLED applications1. Issue 25 (21st March 2015) - Zhao, He; Wang, Yang; Wang, Yongtao; He, Gufeng; Xue, Mei; Guo, Pingan; Dai, Bin; Liu, Zhiyong; Qi, Yu
<x xml:space="preserve">Abstract</x> Well-designed AIE-active luminogens as both hole-transporting and light-emitting layer materials can be utilized to fabricate metal free and nondoped OLEDs.